Effects of adding dexmedetomidine to nebulized lidocaine on control of hemodynamic responses to laryngoscopy and intubation: A randomized clinical trial - Bhavna Sriramka; Zeeshan Haider Warsi; Janmejaya Sahoo (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Hemodynamic responses (HDR) to laryngoscopy and intubation are a significant concern for the anesthesiologist. This study aimed to compare the effects of intravenous Dexmedetomidine and nebulized Lidocaine for control of HDR to laryngoscopy and intubation when used in combination or alone. Material and Methods: This double-blind, parallel group, randomized clinical trial included 90 patients (30 for each group) aged 18-55 years with ASA grade 1-2. Group DL received intravenous (IV) Dexmedetomidine (1 μg kg-1) and nebulized Lidocaine 4% (3 mg kg-1) before laryngoscopy. Group D received IV Dexmedetomidine (1 μg kg-1) and group L received nebulized Lidocaine 4% (3 mg kg-1). Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were recorded at baseline, post nebulization, and at 1, 3, 5, 7, and 10 min post-intubation. Data analysis was done by SPSS 20.0. Results: Post-intubation HR was better controlled in group DL than group D and group L (76.40 ± 5.61, 95.16 ± 10.60, 103.90 ± 12.98 respectively, P value <0.01). Group DL > D > L controlled SBP changes significantly (118.93 ± 7.70, 131.10 ± 9.20, 142.66 ± 19.62 respectively, P value <0.01). At 7 and 10 minutes, group D and L found similarly effective in preventing a rise in SBP. Group DL showed significantly better control of DBP than group L and D till 7 minutes (P < 0.01). Group DL also had better control of MAP post-intubation (92.86 ± 5.50) than group D (102.70 ± 6.64) and L (112.66 ± 7.66) and continued to be better till 10 minutes. Conclusion: We found the addition of intravenous Dexmedetomidine to nebulized Lidocaine to be superior in controlling the increase in HR and MBP post-intubation with no adverse effects.